The Current European Rearmament Between Integration And Fragmentation - Caruso, Raul (Soft Power, 2025)
The purpose of this paper is to examine and discuss the implications of current rearmament, with a particular emphasis on the EU’s initiative for a common defence policy. The ongoing and escalating conflict between Russia and Ukraine has refocused the commitment of European governments and the attention of public opinion on military spending. Notably, defence budgets have been rising significantly. Data from the European Defence Agency (EDA) in 2022 revealed a 6% increase in defence spending compared to the previous year, marking the eighth consecutive year of growth. Since 2022, the conflict between Russia and Ukraine has heavily influenced public discourse, often cementing certain arguments and beliefs without critical examination. This paper aims to analyse three commonly presented theses in greater detail. The first thesis posits that the rearmament announced by various European governments will not only enhance the security of their countries but also contribute to winning the ongoing war by providing military support to Ukraine. The second thesis can be summarized by the phrase "more is better," implying that larger armies and arsenals ensure greater security. The third thesis argues that the current rearmament approach, which focuses on strengthening existing national defence systems, is the best or only possible method. This perspective overlooks potential alternative arrangements, such as an integrated EU defence structure, suggesting that the consolidation of national defence systems would be the optimal choice.